The importance of the make-believe play in early childhood education from the teachers' gaze - Isadhora Araújo Lucena Silva; Maria de Fátima Gomes da Silva (Universidade Federal de Santa Catarina, 2019)
This article is a cut of a master's degree research in education that had as main objective to investigate the contributions of a University Toy Library, created at the University of Pernambuco, with the purpose of promoting Continuing Training for Early Childhood Education teachers and also attending children of this level of schooling, offering them play experiences. The cut presented here is based on the conceptions of teachers from Early Childhood Education, reflecting on the contributions of the makebelieve play for children and for the pedagogical practice, from one of the continuing trainings for teachers developed in the University Toy Library. Through action research, it was possible to conclude that the make-believe play contributes to the learning and development of the child from Early Childhood Education in an imaginative and creative way and that exerts, in the teachers' pedagogical practice, a pedagogical surplus value concerning the necessary interaction between play and learning.